2022
DOI: 10.1111/bjh.18510
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of mitochondrial DNA content in acute promyelocytic leukaemia

Abstract: Summary Although a growing body of evidence demonstrates that altered mtDNA content (mtDNAc) has clinical implications in several types of solid tumours, its prognostic relevance in acute promyelocytic leukaemia (APL) patients remains largely unknown. Here, we show that patients with higher‐than‐normal mtDNAc had better outcomes regardless of tumour burden. These results were more evident in patients with low‐risk of relapse. The multivariate Cox proportional hazard model demonstrated that high mtDNAc was inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Enhanced mtDNA copy number has been previously reported to be play role on AML initiation, progression as well as predictive of inferior survival outcomes ( 12 , 36 ). A contrasting finding was recently observed in patients of AML M3 subgroup where elevated mtDNA copy number was predictive of superior survival outcome ( 37 ), however, AML M3 subgroup has a distinct disease biology and is not directly comparable with other AML subgroups ( 38 ). On the other hand, similar to our previous finding ( 12 ), we observed that mtDNA copy number were significantly higher and independently predictive of worse survival outcome in this cohort of pediatric AML patients as well.…”
Section: Discussionmentioning
confidence: 78%
“…Enhanced mtDNA copy number has been previously reported to be play role on AML initiation, progression as well as predictive of inferior survival outcomes ( 12 , 36 ). A contrasting finding was recently observed in patients of AML M3 subgroup where elevated mtDNA copy number was predictive of superior survival outcome ( 37 ), however, AML M3 subgroup has a distinct disease biology and is not directly comparable with other AML subgroups ( 38 ). On the other hand, similar to our previous finding ( 12 ), we observed that mtDNA copy number were significantly higher and independently predictive of worse survival outcome in this cohort of pediatric AML patients as well.…”
Section: Discussionmentioning
confidence: 78%
“…In their paper, Pereira‐Martins et al 1 demonstrate that acute promyelocytic leukaemia (APL) patients treated with chemotherapy and all‐ trans retinoic acid (ATRA) whose leukaemia cells had increased mitochondrial DNA content had a significantly lower cumulative incidence of relapse than patients with normal mitochondrial DNA levels. Although mitochondrial DNA's influence on the pathogenesis of lung cancer, oral cancer and a number of other solid tumours 2,3 as well as some non‐malignant diseases such as Alzheimer's 4 has been extensively studied, investigations in acute leukaemia have only recently been reported.…”
mentioning
confidence: 99%